High-specific-capacitance electrolytic capacitors based on anodic TiO2 nanotube arrays. (10th October 2022) - Yu, Yuantian; Li, Chengyuan; Wang, Heng; Chen, Jieda; Zhu, Xufei; Ying, Zongrong; Song, Ye
Highlights: New electrolytic capacitors based on TiO2 nanotube arrays (TDNAs) were developed. Anodized TDNAs were transformed into titanium nitride nanotube arrays (TNNAs) by nitridation. The fabricated BaTiO3 @TNNAs were employed as anode of the electrolytic capacitor. The capacitor cathode was derived from the TDNAs by an electrochemical doping route. The new capacitors exhibit a high capacitance of 292.8 μF cm −2 for 2.6-μm-thick TNNAs. Abstract: Electrolytic capacitors have been increasingly used in almost all electronic devices because of their large specific capacitance, broad operating voltage range and good price to performance ratio. To satisfy the continuing miniaturization trend of electronic devices, researchers have continuously maintained efforts to increase the specific capacitance of electrolytic capacitors. Herein, we report a novel way to achieve high-specific-capacitance electrolytic capacitors starting from titanium dioxide nanotube arrays (TDNAs) formed by anodization. The anodized TDNAs are first transformed into titanium nitride nanotube arrays (TNNAs) by nitridation. Then TNNAs covered with a BaTiO3 film (BaTiO3 @TNNAs) are obtained through electrochemical deposition and subsequent annealing. Thus, the fabricated BaTiO3 @TNNAs are employed as anode of an electrolytic capacitor. The capacitor cathode is also derived from the anodized TDNAs by an electrochemical doping approach. The capacitor made of the BaTiO3 @TNNAs anode and TDNAs cathode shows excellent electrical properties with a high specific capacitance of 292.8 μF cm −2, considerably higher than previously reported values for the modified aluminum anode foils. This study can provide new directions in increasing specific capacitance of electrolytic capacitors. Graphical abstract: Image, graphical abstract